Pelatihan digital bisnis marketing melalui bauran pemasaran pada Bank Syariah Indonesia Lamongan - Darmayanti, Novi; Sari, Dian Puspita; Pramesti, Renita; Baiti, Isma Nur; Wahyuni, Mira (Nur Science Institute, 2025)
Banking institutions have made rapid progress in efforts to support the continuation and improvement of the implementation of reliable and healthy banking services. The products offered by Bank Syariah Indonesia include banking services, hajj savings, easy wadiah and mudharabah, gold installments and pawns, deposits, and KUR applications. The problem with this service is a limitation in employee knowledge about the business digital marketing mix, so a problem arises in human resources, customer service, and BSI's digitalization system. The Implementation Method is a deep interview. The solution to solve the problem is to conduct training for BSI employees by sharing broader and specific information about digital banking marketing to keep up with the times. An effective and reliable marketing strategy is required to create customer value and build strong and profitable relationships.